Factors that affect student performance: the implementation of the i-learn at a local university - Setapa, Mariam; Mohammad, Noorita; Rahman, Khairunnisa (Institut Pengurusan Penyelidikan, 2012)
The purpose of this study is to identify factors affecting the usage of i-Learn at Universiti Teknologi MARA (UiTM) and its impact on students' performance. Drawing from a study by Hafizah Mohamad Hsbollah and Kamil Md. Idris (2009), which identified six factors influencing e-learning usage among lecturers, this study examines these factors—specifically technological features and individual characteristics—from the perspective of university students. A pilot study conducted on 20 students at UiTM Johor revealed that while students are aware of the system, they do not fully utilize it for various reasons. Consequently, this study aims to identify the factors affecting i-Learn usage and determine the most dominant factor influencing usage and student performance. Data were collected from 60 Semester 1 (Part 1) students at UiTM Johor, consisting of two groups. A pilot test was conducted with 20 students to validate the questionnaire. Internal consistency was measured using Cronbach’s Alpha, and exploratory factor analysis was used to verify the measurements. Additionally, correlation and regression methods were employed to identify the relationship between the variables and determine the dominant factors. The expected result of this study is to demonstrate a clear correlation between the reviewed factors and student performance.